Пошаговое объяснение:
-9 + (-3.5) =-9-3.5=-12.5
-0.6 + ( -1/2 ) + 0.7 =-0.6-0.5+0.7=-0.4
-3.8 + (-5.4 ) =-3.8-5.4=-9.2
-0.75 + ( - 4/5 ) + 0.9=-0.75-0.8+0.9=-0.65
-9 + (-3.5) =-12.5
-0.6 + ( -1/2 ) + 0.7=-0.4
-3.8 + (-5.4 )=-9.2
Пошаговое объяснение:
-9 + (-3.5) =-9-3.5=-12.5
-0.6 + ( -1/2 ) + 0.7 =-0.6-0.5+0.7=-0.4
-3.8 + (-5.4 ) =-3.8-5.4=-9.2
-0.75 + ( - 4/5 ) + 0.9=-0.75-0.8+0.9=-0.65
-9 + (-3.5) =-12.5
-0.6 + ( -1/2 ) + 0.7=-0.4
-3.8 + (-5.4 )=-9.2
-0.75 + ( - 4/5 ) + 0.9=-0.75-0.8+0.9=-0.65